SYNERGY OF EFFECTIVE POWER SECTOR AND TOWN PLANNING UNIT (FULafia Journal of Science and Technology, 2018)
The ever-increasing population in Nigeria brings to bare, the need for enhanced social amenities. This is because, no matter the population upsurge, everyone desires to enjoy at least the minimum comfort. While the need for comfort cannot be overemphasised, there is again the need for survival onnecessities likeElectricity supply which also plays a very vital and strategic role in the economic development. In view of the fact that electricity supply is not sufficient to meet expecteddemands, several vices are introduced in its supply chain. Key among this is the illegal connections which affects the national grid supply.This paper investigated the  rolesutility companies play in ensuringcompliance of standards and the role of the town planning team in the environmental management of the enforcement and recommends a synergy of efforts between the two parties for effective and qualitative service delivery
Keywords: Town; Planning; Electricity; Development; PHCN